The Effect of Superficial Heat-Cold Application on the Sleep Quality of Patients With Restless Leg Syndrome: A Systematic Review and Meta‐Analysis - Mohammad Mehdi Mohammadi; Maryam Ahmadi; Ali Akbar Vaisi Raygani (Wiley, 2024)
ABSTRACT Aim The present study was conducted to determine the effect of the superficial heat-cold application on the sleep quality of patients with restless leg syndrome. Design This study was a systematic review and meta‐analysis. Methods In the present study, the electronic databases Scopus, ProQuest, Web of Science, PubMed, SID and Google Scholar were searched from their inception to September 2023. The quality of included studies was evaluated through the Cochrane Collaboration's Risk of Bias Tool, and finally, a meta‐analysis was conducted by calculating standardised mean differences (SMDs). Results The meta‐analysis results revealed that superficial heat-cold application improved sleep quality in patients with RLS (SMD = 0.685, 95% CI: 0.421-0.950). The meta‐regression results showed that as the temperature increased, the intervention was more effective in improving sleep quality (β = 0.0182, 95% CI: 0.0096-0.0268, p < 0.05). Moreover, the effectiveness of the intervention in improving the sleep quality of patients with RLS reduced significantly as the duration of intervention in each session (β = −0.031, 95% CI: −0.059 to −0.001, p < 0.05) as well as participants' age increased (β = −0.013, 95% CI: −0.024 to −0.001, p = 0.0259). Patient or Public Contribution This research showed that superficial heat-cold application had the capability to improve the sleep quality of patients with restless leg syndrome. In addition, in this study, settings were suggested according to which the maximum effectiveness of the intervention could be achieved.